Depression and Sequential Decision-Making Revisited - Sander, Martha; Nestler, Steffen; Egloff, Boris (Frontiers in Psychology, 2019)
Background: The effect of depression on decision making is an important but still unsettled issue. Whereas most studies have reported that clinically depressed participants show worse performance, there are also studies that have shown no or even positive effects. Specifically, von Helversen et al. (2011) were able to document a positive effect of depression on task performance in a sequential decision-making task called the secretary problem. Here, we (a) aimed to replicate this study in an extended version using more trials and (b) modified it by including an additional condition in which negative feedback was given. Method: 82 participants took part. They were split in two groups à 20/21 participants with Major Depression Disorder (MDD) and two groups à 20/21 matched healthy participants. Participants completed the secretary problem either in the standard or in a modified version. Additionally, they answered questionnaires for assessing depression, personality and intelligence. Results: We did not find any significant differences between clinically depressed and nondepressed individuals in any indicators of task performance, under both the original and modified conditions. Limitations: Our participants were ambulatory patients. The quality of depression may have been therefore less extreme. We did not assess or control for rumination. Conclusions: We were not able to detect any significant differences between the performances of healthy and clinically depressed participants in a sequential decision-making task.